2021
DOI: 10.4103/ijo.ijo_956_20
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on endothelial cell loss in nanophthalmic eyes undergoing cataract surgery by phacoemulsification

Abstract: Purpose: The purpose of this study is to compare the endothelial cell loss (ECL) in nanophthalmic eyes and age-matched controls undergoing cataract surgery by phacoemulsification and also to identify the risk factors influencing the endothelial cell density (ECD). This was a prospective comparative interventional case series. Methods: We enrolled 19 nanophthalmic eyes (study group) and 42 age-matched cataract controls (control group) undergoing phacoemulsification after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Jung and colleagues reported higher rates of endothelial cell loss in nanophthalmos (14.2%) compared to normal controls (7.6%), however, the difference was not statistically significant (P ¼ 0.54) [7]. A recent study by Rajendrababu and colleagues found that nanophthalmic eyes with AC depth <2.5 mm have a significantly greater reduction in endothelial cell density as compared to agematched controls (P ¼ 0.03) [48].…”
Section: Endothelial Cell Loss and Postoperative Corneal Edemamentioning
confidence: 97%
See 2 more Smart Citations
“…Jung and colleagues reported higher rates of endothelial cell loss in nanophthalmos (14.2%) compared to normal controls (7.6%), however, the difference was not statistically significant (P ¼ 0.54) [7]. A recent study by Rajendrababu and colleagues found that nanophthalmic eyes with AC depth <2.5 mm have a significantly greater reduction in endothelial cell density as compared to agematched controls (P ¼ 0.03) [48].…”
Section: Endothelial Cell Loss and Postoperative Corneal Edemamentioning
confidence: 97%
“…Eyes with short AL have an increased likelihood of experiencing complications at or after cataract surgery with studies reporting rates from 5.3 to 27.9% [47][48][49]. Day and colleagues reported a complication rate of 15.5% (16/103 eyes) including zonular dehiscence, aqueous misdirection, severe uveitis, IOL-related complications, and choroidal effusion.…”
Section: Intra-and Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eyes with short axial length (AL) are characterized by a shallow AC, narrow angle and thick lens. PKE in patients with short AL is very challenging because of their compacted anterior segment and limited space for maneuvers [ 62 , 63 , 64 ]. Maintaining a stable AC is crucial there, as a fluctuating IOP, especially a low IOP, greatly increases the risk of choroidal detachment, hemorrhage and PC rupture [ 15 ].…”
Section: Afs In Complicated Conditionsmentioning
confidence: 99%
“…Additional precautions are required when treating nanophthalmic eyes with concomitant ocular conditions. Cataract surgery in these patients is challenging, and may result in poor visual outcomes and complications such as uveal effusion, retinal detachment, and corneal decompensation [ 47 ]. In one study of 114 nanophthalmic eyes undergoing cataract surgery, 29 eyes had complications, of which uveal effusion accounted for half [ 48 ].…”
Section: Ues Risk and Prophylaxis In Nanophthalmic Patientsmentioning
confidence: 99%